Agreement between 24-h dietary recalls and 24-h urine collections for estimating sodium intake in China, Japan, UK, USA: the International Study of Macro- and Micro-nutrients and Blood Pressure. Issue 4 (April 2019) - Wen, Xiaoxiao; Zhou, Long; Stamler, Jeremiah; Chan, Queenie; Van Horn, Linda; Daviglus, Martha L.; Dyer, Alan R.; Elliott, Paul; Ueshima, Hirotsugu; Miura, Katsuyuki; Okuda, Nagako; Wu, Yangfeng; et al.
Abstract : Objective: The present study aims to compare 24-h dietary recalls with 24-h urine collections for the estimation of sodium intake at both population and individual levels in China, Japan, the United Kingdom (UK), and the United States of America (USA), using data from the International Study of Macro- and Micro-nutrients and Blood Pressure (INTERMAP). Methods: Mean differences between 24-h dietary recalls and 24-h urine collections were calculated for their agreement in estimating sodium intake at the population level; relative and absolute differences as well as misclassification of salt intake groups (salt intake <6, 6–8.9, 9–11.9, 12–14.9, and ≥15 g/day) were used to determine the agreement at the individual level. Results: The mean differences (95% CI) between dietary recalls and urine collections for China, Japan, UK, and USA were −54.0 (−59.8, −48.3), 3.9 (0.6, 7.2), 2.9 (−1.8, 7.6), and −3.5 (−5.8, −1.1) mmol/day, respectively. The proportions of individual relative differences beyond ±40% were 34.3% for China, 16.9% for Japan, 24.2% for UK, and 21.3% for USA; the proportions of individual absolute differences greater than 51.3 mmol/day (3 g salt) were 58.6% for China, 32.8% for Japan, 25.4% for UK, and 31.9% for USA. The rate for misclassification of salt intake groups at individual level for China, Japan, UK, and USA were 71.4, 60.9, 58.7, and 60.0%, respectively. Conclusion: The 24-h dietary recalls demonstrate greater agreement with the 24-h urine collections in estimating population sodium intake for Japan, UK, and USA, compared with China. The 24-h dietary recall has poor performance in assessing individual sodium intake in these four countries. Abstract : Supplemental Digital Content is available in the text